Implementation of the Policy of Equalizing Administrative Positions to Functional Positions in the Development Administration Bureau of the Regional Secretariat of the Province of North Sulawesi - John Andreas Wuwung,; Goinpeace H. Tumbel,; Laurens Bulo, (Technium Social Sciences Journal, 2025)
This research aims to find out, describe and analyze the Implementation of the Equalization Policy of Administrative Positions to Functional Positions at the Bureau of Development Administration of the Regional Secretariat of North Sulawesi Province and its determinants. This research uses a qualitative approach. The results showed that: (1) Employee Competencies and Qualifications: the gap between the competencies possessed by employees and the demands of functional positions is the main inhibiting factor; (2) Structure and Work System: the division of tasks and allocation of resources that are not in accordance with the needs of functional positions cause employees to still carry out administrative tasks, not more technical functions; (3) Organizational Culture: organizational culture that prioritizes administrative procedures and rigid hierarchies hinders the process of changing towards functional positions that are more analytical and data-based; Furthermore, Determinant Factors: (1) Supportive Regulations and Policies: the absence of regulations that support and emphasize the implementation of functional duties; (2) Availability of Resources: limited budget, facilities and infrastructure and experts are one of the influencing factors. (3) Evaluation and Supervision System: performance evaluation is not yet relevant to the needs and supervision tends to be more administrative. Overall, the policy has been implemented but not optimized.